PENGGANTIAN BOVINE SERUM ALBUMIN PADA PENGENCER CEP-2 DENGAN SERUM DARAH SAPI DAN PUTIH TELUR TERHADAP KUALITAS SEMEN CAIR SAPI LIMOUSIN SELAMA PENDINGINAN (The Substitution of Bovine Serum Albumin with Cattle Blood Serum and Egg White in CEP-2 Diluent on the Quality of Limousin Bull Liquid Semen during Refrigerating) - Susilawati, Trinil; Wahyudi, Feri Eka; Anggraeni, Inna; Isnaini, Nurul; Ihsan, Muhammad Nur (Universitas Syiah Kuala, 2016)
This study aims to determine the effect of the substitution of bovine serum albumin (BSA) with cattle blood serum and egg white in the diluent of Cauda epididymal Plasma 2 (CEP-2) on sperm quality of Limousin cattle during cooling at 3-5 C. The research material used was rejected Limousin bull sperm (motility of 50-60%) from Artificial Insemination Centre Singosari, Malang. This research was a laboratory experiment using a randomized block design which was composed of six treatments with 10 replications, those were T0 as controls ((90% CEP-2 with BSA + 10% egg yolk); T1 (83.84% CEP-2 + 6.16% cattle blood serum + 10% egg yolk); T2 (81.84% CEP-2 + 8.16% cattle blood serum + 10% egg yolk); dan T3 (90% CEP-2 + 0,4% egg white + 10% egg yolk); T4 (90% CEP-2 + 0.8% egg white + 10% egg yolk); and T5 (90% CEP-2 without BSA + 10% egg yolk). Parameters measured were the percentage of motility, viability, and abnormality of sperms. Results of research after 48 hours of storage showed that the percentage of sperm motility in T0, T1, T2, T3, T4, and T5 were 40.505.90, 3636.16, 34.006.58, 40.503.69, 38.503.37, and 38.504.12, respectively, while the percentage of sperms viability were 75.164.30, 70.502.88, 73.802.80, 74.803.30, 75.133.13, and 74.034.13, respectively, and the percentage of sperms abnormality were 10.142.34, 10.621.34, 11.332.00, 10.942.82, 10.021.95, and 10.781.96, respectively. In conclusion, CEP-2 diluent with or without the addition of 19% egg yolk in BSA and the substitution of BSA with 0.4-0.8% egg white can maintain semen quality to hour of 48 in cold storage.This study aims to determine the effect of the substitution of bovine serum albumin (BSA) with cattle blood serum and egg white in the diluent of Cauda epididymal Plasma 2 (CEP-2) on sperm quality of Limousin cattle during cooling at 3-5 C. The research material used was rejected Limousin bull sperm (motility of 50-60%) from Artificial Insemination Centre Singosari, Malang. This research was a laboratory experiment using a randomized block design which was composed of six treatments with 10 replications, those were T0 as controls ((90% CEP-2 with BSA + 10% egg yolk); T1 (83.84% CEP-2 + 6.16% cattle blood serum + 10% egg yolk); T2 (81.84% CEP-2 + 8.16% cattle blood serum + 10% egg yolk); dan T3 (90% CEP-2 + 0,4% egg white + 10% egg yolk); T4 (90% CEP-2 + 0.8% egg white + 10% egg yolk); and T5 (90% CEP-2 without BSA + 10% egg yolk). Parameters measured were the percentage of motility, viability, and abnormality of sperms. Results of research after 48 hours of storage showed that the percentage of sperm motility in T0, T1, T2, T3, T4, and T5 were 40.505.90, 3636.16, 34.006.58, 40.503.69, 38.503.37, and 38.504.12, respectively, while the percentage of sperms viability were 75.164.30, 70.502.88, 73.802.80, 74.803.30, 75.133.13, and 74.034.13, respectively, and the percentage of sperms abnormality were 10.142.34, 10.621.34, 11.332.00, 10.942.82, 10.021.95, and 10.781.96, respectively. In conclusion, CEP-2 diluent with or without the addition of 19% egg yolk in BSA and the substitution of BSA with 0.4-0.8% egg white can maintain semen quality to hour of 48 in cold storage.